Penggunaan Media Interactive Flat Panel (IFP) oleh Guru PAI dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran PAI di SMP IT Al Wafa Godo Kabupaten Bima - Iwansyah Iwansyah; Nasaruddin Nasaruddin; Kaharuddin Kaharuddin (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to describe the use of Interactive Flat Panel (IFP) media by Islamic Religious Education (PAI) teachers in an effort to increase students’ learning motivation at SMP IT Al Wafa Godo, Bima Regency. In addition, this study seeks to examine students’ responses to the use of IFP and to identify the factors that support and hinder its implementation. This research employed a descriptive method with a qualitative approach, while data were collected through observation, interviews, and documentation. The results of the study show that the use of IFP in PAI learning was carried out through three stages: planning, implementation, and evaluation. In the planning stage, the teachers prepared lesson plans that integrated the use of IFP. In the implementation stage, the teachers applied an expository strategy supported by instructional videos and interactive quizzes. Meanwhile, in the evaluation stage, the teachers utilized Kahoot and Wordwall as interactive assessment platforms. Students’ responses to the use of IFP were highly positive, as indicated by increased enthusiasm, greater ease in understanding the material, and the expectation that IFP would also be used in other subjects. The supporting factors for IFP implementation included school policy support, teachers’ digital competence, and the availability of learning infrastructure. Meanwhile, the inhibiting factors included teachers’ limited preparation time in developing digital materials, differences in digital competence among teachers, and the limited number of available IFP devices. Thus, this study concludes that IFP is effective in increasing students’ learning motivation in PAI subjects. However, optimizing its use still requires additional devices, continuous teacher training, and better management of learning time.